EFFECT OF ZEOLITE ON NUTRIENTS EFFICIENCY OF COMPOST IN THE SOIL - Lenny M. Estiaty; Suwardi Suwardi; Isti Yuliana; Dewi Fatimah; Dadan Suherman (Jurnal Zeolit Indonesia, 2005)
Manure contains micro and macro nutrients which are essential for plant growth. During the decomposition process and after application to the soil, nutrients in manure especially nitrogen is easily volatile to the atmosphere and leaching by water. Zeolite has a high adsorption to ammonium ion, so the application of zeolite together with manure may improve the plant growth. The objective of this research is to evaluate the effect of manure and zeolite addition to the growth and absorption of plant nutrients of Ipomoea reptans. This research was conducted in green house of Department of Soil Science, Faculty of Agriculture, Bogor Agricultural University, from June until October 2004. Cultivation was conducted in two period. Immediately after the plant were harvested in first period, plant media were cultivated for the second period without addition of fertilizers. Addition of 20 ton/ha zeolite to the plant media influence the growth and absorption of nutrient higher than the other zeolite treatments. Nutrient residue of zeolite treatment is higher than the treatment without zeolite which is shown by higher production of Ipomoea reptans in the second planting period. Application of zeolite increase the growth of plant. Application of zeolite together with chicken manure gave higher growth and production compared with cattle manure.